Gaseous Mediators as a Key Molecular Targets for the Development of Gastrointestinal-Safe Anti-Inflammatory Pharmacology - Danielak, Aleksandra; Wallace, John L; Brzozowski, Tomasz; Magierowski, Marcin (Frontiers in Pharmacology, 2021)
Non-steroidal anti-inflammatory drugs (NSAIDs) represent one of the most widely used classes of drugs and play a pivotal role in the therapy of numerous inflammatory diseases. However, the adverse effects of these drugs, especially when applied chronically, frequently affect gastrointestinal (GI) tract, resulting in ulceration and bleeding, which constitutes a significant limitation in clinical practice. On the other hand, it has been recently discovered that gaseous mediators nitric oxide (NO), hydrogen sulfide (H2S) and carbon monoxide (CO) contribute to many physiological processes in the GI tract, including the maintenance of GI mucosal barrier integrity. Therefore, based on the possible therapeutic properties of NO, H2S and CO, a novel NSAIDs with ability to release one or more of those gaseous messengers have been synthesized. Until now, both preclinical and clinical studies have shown promising effects with respect to the anti-inflammatory potency as well as GI-safety of these novel NSAIDs. This review provides an overview of the gaseous mediators-based NSAIDs along with their mechanisms of action, with special emphasis on possible implications for GI mucosal defense mechanisms.